Survey on Recent Researches on High Level Image Retrieval - Vidya, G; Omprakash, S (International Journal of Computer Sciences and Engineering, 2025)
To obtain retrieval accuracy of content based images retrieval systems, the prime notice is on reduction of ‘semantic gaps’ between the visual features and human linguistics than designing low-level feature extraction algorithm. This paper elucidates a comprehensive study on recent technical updates in high-level semantic-based image retrieval. Major recent publications are enclosed during this survey covering different aspects of the research during this space, as well as low-level image feature extraction, similarity mensuration, and deriving high-level linguistics options. We have a tendency to establish 5 major classes of the progressive techniques in narrowing down the‘ linguistics gap’: (1) victimisation object metaphysics to outline high-level concepts; (2) victimisation machine learning ways to associate low-level options with question concepts; (3) victimisation relevance feedback to find out user’s intention; (4) generating linguistics template to support high-level image retrieval; (5) fusing the evidences from markup language text and also the visual content of pictures for computer network image retrieval. Other connected problems reminiscent of image workand retrieval performance evaluation are mentioned.